Dysphagia screening tools for acute stroke patients available for nurses: A systematic review - Isabel de Jesus Oliveira; Liliana Andreia Neves da Mota; Susana Vaz Freitas; Pedro Lopes Ferreira (Tehran University of Medical Sciences, 2019)
Background & Aim: There is a high incidence of dysphagia after stroke that, depending on the assessment, methodology and time elapsed, can range from 8.1% to 80%. Early and systemic dysphagia screening is associated with a decreased risk of aspiration pneumonia and prevents inadequate hydration/nutrition. The purpose of this systematic review was to identify dysphagia screening tools for acute stroke patients available for nurses validated against reference test. The research question was: which dysphagia screening tools for acute stroke patients available for nurses? Methods & Materials: Three electronic databases were searched from January 2007 to November 2017: on PubMed, Scielo and CINAHL Plus. Two independent reviewers screened all titles and abstracts, assessed methodological quality and extracted data. The methodological quality analysis and evaluation was guided according to four domains: patient selection, index test, reference standard and flow and timing. Divergences between reviewers in data extraction were consensualized through discussion. Results: From the 377 articles retrieved, only three articles met criteria for review: Barnes-Jewish Hospital-Stroke Dysphagia Screen; the Gugging Swallowing Screen and, The Toronto Bedside Swallowing Screening Test. None of the screening tools complies with all psychometric properties, which means that a still significant proportion of patients will be kept nil by mouth without being necessary or that some patients will "fall through the cracks" interrupting the diagnostic process. The tools identified are different from each other, making their comparison impracticable. Conclusion: Due to psychometric proprieties and dietary recommendations adjusted to dysphagia severity, of all available tools, GUSS is a suitable screening tool for nurses in clinical practice.